Representation of Military Conflicts in Fashion: The Social Context of Catwalk Shows - Yukhymchuk Anastasiiа; Pashkevych, Kalyna (HUDPROM: The Ukrainian Art and Design Journal, 2025)
The article analyses the evolution of fashion shows and their role in conveying social contexts, particularly in reflecting military conflicts through fashion. The paper explores the key stages in the development and transformation of catwalk presentations within the fashion industry. It is established that fashion serves not only an aesthetic but also a communicative function, with catwalks acting as platforms for broadcasting socially significant ideas. An analysis of fashion collections that reflect the theme of military conflicts, which have become important cultural events, is conducted. It is revealed that contemporary designers, turning to military themes, not only experiment with new artistic approaches but also influence public discourses, drawing attention to issues of war, forced displacement, and national identity. Through the use of symbolic elements, carefully selected color palettes, asymmetrical silhouettes, and stylistic references to military aesthetics, a powerful visual language emerges – one that evokes associations with the past and the shared experiences of society. The study demonstrates that modern fashion does not merely reflect social transformations, but also actively contributes to shaping them. By embodying personal and emotional experiences, designers create conceptual collections that resonate broadly with audiences. Thus, fashion becomes a medium of communication that influences cultural identity, public sentiment, and global discussions, emphasizing the values of peace, solidarity, and human dignity. A special role in this process is played by fashion shows, which function not only as platforms for presenting new collections, but also as significant cultural phenomena. They serve as tools for conveying social, political, and cultural contexts, helping designers articulate ideas and address pressing social issues.